Content Analysis of Diagrams in Secondary School Science Textbooks - Liu, Yang; Treagust, David (Springer, 2013)
This study describes the different types of diagrams contained in nine science textbooks used by Western Australian senior high school students. The content analysis of the textbooks provides information about how diagrams are distributed in different categories of textbooks and the trends in diagrammatic usage in the textbook categories. The first section of the chapter provides the results of the content analysis on the different types of diagrams – iconic, schematic, and charts and graphs – in each of the textbook categories; the second section reveals the distribution of the differences of diagrams in the different textbook categories. In the last section, the trends of diagrammatic usage across school years are discussed. These findings provide useful information for science teachers’ use of diagrams in their planning and execution of secondary science, and in particular biology lessons.